(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The essay deals with the use of the precautionary principle as a criterion for directing the communication of the risks that the same principle is intended to address. After briefly summarizing the current scope of institutional communication on the one hand and of the precautionary principle on the other, we will focus on the application of the typical analysis of the precautionary principle to try to identify how the public decision-maker can direct his or her communication activity. The whole analysis aims at sketching out a legal framework based on the precautionary principle to properly exert risk communication.